Transaksi Valuta Asing (Sharf) dalam Perspektif Islam dan Aplikasinya dalam Bank Syariah - Alfi Amalia; Saparuddin Siregar; Sugianto Sugianto (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the Islamic foreign exchange exchange system (Al-Sharf) in Islamic banks and the views of Islamic banks on foreign currency exchange contracts in accordance with the principles that apply in Islamic teachings (Sharia). This research is a type of descriptive qualitative research, which is to understand deeply about the problem under study by collecting related data and information. The results of this study indicate that; shows that the practice of buying and selling foreign currency (Al-Sharf) according to mu'amalah fiqh is permissible if it is carried out on the basis of willingness between the two parties and in cash (spot) and it is not permissible to add goods of the same kind (gold with gold or silver). with silver). The involvement of Islamic Banks in the application of foreign exchange trading applications, banks are essentially an Intermediary Institution between savers and investors, and Islamic banks are no exception. However, Islamic banks must comply with Sharia provisions based on the Qur'an and Sunnah.